Training on making organic fertilizer (bokashi) as an effort to improve the quality of sustainable plant production in the Taman Seribu Bunga Agrotourism - Dian Tria Fatmila; Kennie Cendekia Desnamrina; Ade Trisna (Journal of Saintech Transfer, 2025)
The Taman Seribu Bunga Agrotourism is a tourist destination known as the beautiful flower beds. The right selection of fertilizer is considered important in the sustainability of agrotourism. The continuous use of chemical fertilizers can cause a decrease in soil health and fertility, which has an impact on plant productivity. In addition, Taman Seribu Bunga Agrotourism is surrounded by farmers who have problems in processing their livestock waste. Therefore, this community service activity carried out is to provide training in bokashi composting as an organic fertilizer that can be used by flower farmers in the Taman Seribu Bunga Agrotourism and its surroundings. The method used is a group discussion forum (FGD), interview, observation, and training using learning media such as brochures, and provide tools and supporting materials for bokashi composting. The results of this study is 6 out of 7 farmers expressed sthat they very satisfied with the bokashi composting training held at Taman Seribu Bunga Agrotourism, highlighting its relevance for managing livestock waste and supporting organic fertilizer needs in local flower and horticultural farming. All 7 farmers also showed interest in applying the knowledge by converting their own farm waste into bokashi. Based on the results of the activity, it can be concluded that the activity can overcome problems related to the accumulation of livestock manure that has not been managed properly.